2017
DOI: 10.2500/ajra.2017.31.4461
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Bacteriology in Patients with Cystic Fibrosis or Primary Ciliary Dyskinesia: A Systematic Review

Abstract: Background: A correlation exists between the microbial flora of the upper and lower airways in patients with cystic fibrosis (CF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…Moreover, a detection rate of 13% was reported for P. aeruginosa by Deschaght et al in 2010 from Belgium in a study conducted on 397 adult and pediatric CF patients (22). The molecular results in our study showed a high rate of colonization with Pseu- nosa was one of the most commonly detected bacteria isolated from noses and sinuses of CF patients (23). This difference could be attributed to various factors, including differences in the frequency of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, a detection rate of 13% was reported for P. aeruginosa by Deschaght et al in 2010 from Belgium in a study conducted on 397 adult and pediatric CF patients (22). The molecular results in our study showed a high rate of colonization with Pseu- nosa was one of the most commonly detected bacteria isolated from noses and sinuses of CF patients (23). This difference could be attributed to various factors, including differences in the frequency of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 56%
“…For this study, the following were the bacterial species we considered clinically “relevant”: P. aeruginosa , Staphylococcus aureus , Achromobacter xylosoxidans , Burkholderia cepacia complex , E. coli , Enterococcus , Streptococcus pneumoniae , Haemophilus influenzae , Proteus mirabilis , Serratia marcescens . Normal flora was defined based on published evidence available, including Neisseria spp., Corynebacterium spp., alpha‐hemolytic streptococci, Rothia spp., coagulase‐negative staphylococci, and non‐hemolytic streptococci, which are commonly considered part of the human nasopharyngeal microbiome …”
Section: Methodsmentioning
confidence: 99%
“…Normal flora was defined based on published evidence available, including Neisseria spp., Corynebacterium spp., alpha-hemolytic streptococci, Rothia spp., coagulase-negative staphylococci, and non-hemolytic streptococci, which are commonly considered part of the human nasopharyngeal microbiome. [25][26][27] For all the patients needing a previously scheduled (graft surveillance based on local protocol) flexible bronchoscopy via the nasal route on the date of baseline visit, additional tests were performed:…”
Section: Nasal Lavagementioning
confidence: 99%
“…Retention and survival of bacteria on toothbrushes after brushing represent a possible cause of re-contamination of the mouth. Several studies [17,21] have shown that prolonged use of the toothbrush facilitates contamination by various microorganisms such as species of Streptococcus, Staphylococcus, Lactobacillus, Pseudomonas, Klebsiella and Candida, and by Escherichia coli. In CF children, P. aeruginosa and S. aureus nasopharyngeal carriage is up to 14%.…”
mentioning
confidence: 99%